Customer Relationship Management (CRM) dan Nilai Pelanggan terhadap Loyalitas Pelanggan - Budiman, Budiman; Muryati, Irnita Ajeng Yuli (Journal the Winners: Economics, Business, Management, and Information System Journal, 2010)
The tourism world today gains a lot of attention and spotlight is greatly increased in many countries and in different places in the world. It is proven by the increasing number of tourist resorts built, due to visitors using the facility. The purpose of this study is to determine whether there is influence of Customer Relationship Management (CRM) on Customer Value at Hotel Crystal, to see if there is influence of CRM on Customer Loyalty at Hotel Kristal, and to find out whether there is influence of Customer Value on Customer Loyalty at Hotel Kristal. The research is descriptive, while the research method used is survey of 100 customers in Hotel Kristal, South Jakarta. Path analyze is used to determine the influence between variables. Result indicates that the CRM provides a positive and significant influence on the Customer Value at Hotel Kristal. Meanwhile, CRM and Customer Value provide a positive and significant influence at Hotel Kristal subsequently affecting Customer Loyalty Hotel Kristal.